Anticancer Activity of Ramalin, a Secondary Metabolite from the Antarctic Lichen Ramalina terebrata, against Colorectal Cancer Cells - Sung-Suk Suh; Tai Kim; Jung Kim; Ju-Mi Hong; Trang Nguyen; Se Han; Ui Youn; Joung Yim; Il-Chan Kim (Molecules, 2017)
Colorectal cancer is a leading cause of death worldwide and occurs through the highly complex coordination of multiple cellular pathways, resulting in carcinogenesis. Recent studies have increasingly revealed that constituents of lichen extracts exhibit potent pharmaceutical activities, including anticancer activity against various cancer cells, making them promising candidates for new anticancer therapeutic drugs. The main objective of this study was to evaluate the anticancer capacities of ramalin, a secondary metabolite from the Antarctic lichen Ramalina terebrata, in the human colorectal cancer cell line HCT116. In this study, ramalin displayed concentration-dependent anticancer activity against HCT116 cells, significantly suppressing proliferation and inducing apoptosis. Furthermore, ramalin induced cell cycle arrest in the gap 2/mitosis (G2/M) phase through the modulation of hallmark genes involved in the G2/M phase transition, such as tumour protein p53 (TP53), cyclin-dependent kinase inhibitor 1A (CDKN1A), cyclin-dependent kinase 1 (CDK1) and cyclin B1 (CCNB1). At both the transcriptional and translational level, ramalin caused a gradual increase in the expression of TP53 and its downstream gene CDKN1A, while decreasing the expression of CDK1 and CCNB1 in a concentration-dependent manner. In addition, ramalin significantly inhibited the migration and invasion of colorectal cancer cells in a concentration-dependent manner. Taken together, these data suggest that ramalin may be a therapeutic candidate for the targeted therapy of colorectal cancer.